Investigating Students Difficulties in Comprehending English Reading Text at the Ninth Grade of SMP IT Qurrota A’yun Palu - Wildan Zahen Da'im; Darmawan Darmawan; Andi Patmasari; Wahyudin Wahyudin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The aim of this study is to identify the most challenging aspect of reading comprehension, particularly in narrative texts, as well as the factors contributing to these challenges. This research adopts a qualitative approach, utilizing tests and interviews as data collection instruments. The participants of this study were students at the junior high school level during the 2024/2025 academic year. A reading comprehension test was administered to 26 students, consisting of 15 questions categorized into five types: identifying the main idea, locating references, understanding vocabulary, making inferences, and finding detailed information. In addition, three students were interviewed using a set of 10 questions. The test findings indicate that the most challenging aspect for the students is identifying detailed information. Furthermore, interview results reveal two main factors contributing to students’ difficulties in reading comprehension: internal and external factors. Internal factors include inadequate reading strategies, limited vocabulary knowledge, and low interest in reading. Meanwhile, the external factor is related to the students’ surrounding environment.